Diagnostic accuracy of immunological methods in patients with tuberculous pleural effusion from Venezuela - Fernández de Larrea, Carlos; Duplat, Aglae; Giampietro, Francesca; de Waard, Jacobus; Luna, Julieta; Singh, Mahavir; Araujo, Zaida (Investigación Clínica, 2011)
In recent years, better diagnostics for tuberculosis (TB) has received increasing attention, especially the diagnosis of tuberculous pleural effusion, which is difficult and at present the main tool in TPE diagnostic is pleural effusion smear and culture, but unfortunately, sensitivities are low, therefore better TPE diagnostic tools are needed. The aim of this study was to find a diagnostic algorithm to assess the progress in TPE diagnostic at the Hospital Vargas de Caracas, that permits identification of the majority of patients, at a satisfactory cost-benefit ratio, evaluating the levels of IFN-ïŸï€ and IL-12p40 in pleural effusion and serum, as well as the antibody reactivity in order to compare it with microbiological tests. A total of 60 individuals with pleural effusion were studied; 20 patients with tuberculous pleural effusion (TPE) formed the patient group and 40 patients with non-tuberculous pleural effusion (NTPE) formed the control group. The levels of IFN-ïŸï€ and IL-12p40 in effusion and serum and class and subclasses of IgG reactivity to Mycobacterium tuberculosis antigens were measured by ELISA. The utility of these methods for diagnosis of TPE was evaluated using receiver operating characteristic (ROC) curve analysis. The results of the 11 immunological methods evaluated showed that the anti-PPD IgG2 method was able to reach the highest specificity of 95% (CI: 88.3-101.8), positive predictive value (PPV)=75 (at 30% sensitivity); while that the overall sensitivity of methods was between 95% and 30%, of these, two methods reached higher sensitivities; increased levels of pleural IFN-ïŸ, with a sensitivity of 95% (CI: 85.5-104.5) with the highest negative pre- dictive value (NPV)=97, (at 82.5% specificity), followed by decreased levels of serum IL-12p40 with a sensitivity of 95% (CI: 85.5-104.5), NPV=95.2 (at 50% specificity). In contrast, microbiological methods showed that smear had a sensitivity of only 20%, while smear plus culture had, a sensitivity of 70%. Considering that TPE represents approximately 15 percent of all the TB clinically diagnosed at the Hospital Vargas de Caracas, in those patients with preliminary microbiology negativity in the effusion, the combined analysis of pleural IFN-ïŸï€ and anti-PPD IgG2 could represent a fast and effective diagnostic algorithm for improving the diagnosis previous to obtain culture results. In this way treatment against TB could be initiated or the need to cytological and pleural biopsy could be considered.